A DFT study on the electronic structure of in-plane heterojunctions of graphene and hexagonal boron nitride nanoribbons. (7th June 2021) - dos Santos, Ramiro M; Giozza, William F; de Sousa Junior, Rafael T; da Silva Filho, Demétrio A; Santos, Renato B; Ribeiro Júnior, Luiz A
Abstract: The structural similarity between hexagonal boron nitride (h-BN) and graphene nanoribbons allows forming heterojunctions with small chain stress. The insulation nature of the former and the quasi-metallic property of the latter make them attractive for flat optoelectronics. Recently, shapes of graphene and h-BN domains were precisely controlled, creating sharp graphene/h-BN interfaces. Here, we investigated the electronic and structural properties of graphene (h-BN) nanoribbon domains of different sizes sandwiched between h-BN (graphene) nanoribbons forming in-plane heterojunctions. Different domain sizes for the non-passivated zigzag edge termination were studied. Results showed that the charge density is localized in the edge of the heterojunctions, regardless of the domain size. The systems with graphene domains are metallic, presenting null band gaps. The ones with the h-BN island are small-bandgap semiconductors with the highest bandgap value around 0.2 eV. The calculated bandgap has the same magnitude of the certain threshold for density functional theory. As a general trend, these materials exhibit a ferromagnetic behavior, which can be useful for magnetic applications at the nanoscale.